ANALISIS BEBAN KERJA PEGAWAI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Teddy Marliadi Nurwan (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2017)
This study aims to obtain an overview of the workload at the District Office Cimalaka Sumedang, to determine the factors that hinder the workload at the District Office Cimalaka Sumedang, to know what efforts are made Subdistrict Cimalaka Sumedang in addressing the factors inhibitors workload.Techniques of collecting samples used in this research is purposive sampling techniques, the sampling technique based on need.Then the samples in this study were 1 sub-district and 1 Sekcam, 1 Head, 2 Civil Servants (PNS). The author draws the conclusion that the workload at the District Office Sumedang Cimalaka overall that the tasks performed physical labor organizations such as the time period of work, the working environment is the physical work environment, fInternal actors like, factors from the body as a result of reaction to the workload of the external factors that hamper the workload at the District Office Cimalaka Sumedang is because the burden is too heavy, physical work load with time, the imposition of excessive so as to affect the performance of employees in ultimately the goal will not be achieved as service to the community to be weak, efforts undertaken District of Cimalaka Sumedang in overcoming the limiting factors workload is a target to be achieved well, the working conditions are supportive of all employees and jobs and standard of work pass the required quality standards of the State civil apparatus set forth in legislation ASN.The suggestions writer is should the District Cimalaka in this case camat more attention to employees who often excel in attendance and work by providing promotional opportunities are fair and based on seniority, promotion of fair and based on performance, the existence of the bonus given when the results of such work achieve targets such as remuneration based on individual skill levels, remuneration based on work results achieved servants,The promotion of staff to the structural organization is giving employees who have served for a long time because of obstruction by the education factor so defeated by new employees with education is high in this case the boss always gives feedback to subordinates therefore leaders should always create communication between subordinates and tops are good.